PENERAPAN METODE VAKT (VISUAL, AUDITORY, KINESTHETIC, TACTILE) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS 3 SD - Andriani, Yuli; Hendiawan, Deri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading proficiency is the fundamental cornerstone of the educational process, yet many third-grade students continue to face substantial hurdles in early literacy, often categorized as "low-readers." This study investigates the implementation of the VAKT (Visual, Auditory, Kinesthetic, and Tactile) multisensory method as a strategic intervention to accelerate letter and word recognition. The objective of this research is to evaluate the effectiveness of engaging multiple sensory channels simultaneously to overcome cognitive difficulties and rebuild students' academic self-confidence.This research utilizes a quantitative approach with a pre-experimental design involving ten third-grade students. Data were collected through pre-test and post-test assessments and analyzed using the Paired Samples T-Test via SPSS software. The statistical analysis indicates a significant improvement in students' reading abilities. The mean score increased from 84.70 in the pre-test to 92.00 in the post-test. The Paired Samples T-Test yielded a significance value of p < 0.001, which is lower than the alpha level of 0.05, thereby confirming that the VAKT method has a statistically significant impact. Furthermore, the effect size measured by Cohen’s d was -1.641, indicating a "Large Effect" of the intervention.The discussion suggests that integrating tactile and kinesthetic stimuli—such as tracing textured letters—provides a "cognitive anchor" that helps students distinguish visually similar characters. In conclusion, the VAKT method is a highly effective remedial tool for addressing reading delays in the third grade and fostering an inclusive learning environment. Keywords: VAKT Method, Early Reading, Multisensory Learning. Reading proficiency is the fundamental cornerstone of the educational process, yet many third-grade students continue to face substantial hurdles in early literacy, often categorized as "low-readers." This study investigates the implementation of the VAKT (Visual, Auditory, Kinesthetic, and Tactile) multisensory method as a strategic intervention to accelerate letter and word recognition. The objective of this research is to evaluate the effectiveness of engaging multiple sensory channels simultaneously to overcome cognitive difficulties and rebuild students' academic self-confidence.This research utilizes a quantitative approach with a pre-experimental design involving ten third-grade students. Data were collected through pre-test and post-test assessments and analyzed using the Paired Samples T-Test via SPSS software. The statistical analysis indicates a significant improvement in students' reading abilities. The mean score increased from 84.70 in the pre-test to 92.00 in the post-test. The Paired Samples T-Test yielded a significance value of p < 0.001, which is lower than the alpha level of 0.05, thereby confirming that the VAKT method has a statistically significant impact. Furthermore, the effect size measured by Cohen’s d was -1.641, indicating a "Large Effect" of the intervention.The discussion suggests that integrating tactile and kinesthetic stimuli—such as tracing textured letters—provides a "cognitive anchor" that helps students distinguish visually similar characters. In conclusion, the VAKT method is a highly effective remedial tool for addressing reading delays in the third grade and fostering an inclusive learning environment.